Extent, Distribution, and Causes of Soil Acidity under Subsistence Farming System and Lime Recommendation: The Case in Wolaita, Southern Ethiopia - Fanuel Laekemariam; Kibebew Kibret (Applied and Environmental Soil Science)
Soil acidity is one of the most important environmental threats to the Ethiopian highlands where the livelihood of the majority of people is reliant on agriculture. Yet, information regarding its extent, distribution, causes, and lime requirement at a scale relevant to subsistence farming systems is still lacking. This study (1) investigates the extent and spatial distribution of soil acidity, (2) identifies factors attributing to soil acidification, and (3) predicts the lime requirement for major crops. A total of 789 soil samples were collected from arable lands in the Wolaita area which is mainly characterized by poor soil fertility and soil degradation in southern Ethiopia. Results revealed that the landscape is characterized by a gentle slope followed by strongly sloppy > flat > hilly topographies. Clay is the dominant soil textural class. A soil pH map, which is generated using geospatial analysis, demonstrates that 3.3, 78.0, and 18.7% of the total area were under strongly acidic, moderately acidic, and neutral soil reactions, respectively. The exchangeable acidity (Cmol(+)/kg) varied from nil to 5.1, whereas exchangeable Al ranged from 1.4 to 19.9 Cmol(+)/kg. The soil pH has shown a significantly (p < 0.001) negative association with clay content (r = −0.33), exchangeable Al (r = −61), exchangeable acidity (r = −0.58), and inorganic fertilizer application (r = −0.33). Increased rates of diammonium phosphate (DAP) (r2 = 0.91) and urea (r2 = 0.88) markedly elevated soil acidity. Conversely, manuring showed a significant (p < 0.001) and positive relationship with pH (r = 0.37) in which the increasing rate of manure significantly reduced acidification (r2 = 0.98). DAP and urea applications above 75 kg/ha lowered soil pH units by 0.56 and 0.48, respectively, <25 kg/ha while at the same time farmyard manure (FYM) at 4 t/ha raised pH by 0.75 units over the unfertilized field. Residue management significantly (p < 0.001) influenced soil pH wherein it ranged from 6.09 (complete residue removal) to 6.61 (residue incorporation). Changes in land use, cropping intensity, and socioeconomic status were also significantly attributed to soil acidification. To curb the effects of soil acidity, the lime requirement for common bean growing fields varied from zero to 6.6 t/ha, while for maize it was between zero and 4.3 t/ha. It is concluded that soil management interventions such as maintaining and incorporating crop residues, integrated use of organic and inorganic fertilizers, liming, and enhancing farmers’ awareness should be advocated to overcome soil acidification and improve soil fertility. In addition, introducing crops with traits that tolerate acidity and Al toxicity is also suggested.